Reviewer Acknowledgements for Environmental Management and Sustainable Development, Vol. 10 No. 1 - Young, Jenny (Environmental Management and Sustainable Development, 2021)
Environmental Management and Sustainable Development (EMSD) would like to thank the following reviewers for reviewing manuscripts from November 1, 2020, to February 1, 2021. Their comments and suggestions were of great help to the authors in improving the quality of their papers. Many authors, regardless of whether EMSD publishes their work, appreciate the helpful feedback provided by the reviewers. Macrothink Institute appreciates the following reviewers’ rigorous and conscientious efforts for this journal. Each of the reviewers listed below returned at least one review during this period. Adriano Magliocco, University of Genoa, Italy Anna Rita Bernadette Cammerino, University of Foggia, Italy Christiane do Nascimento Monte, Universidade Federal Fluminense, Brazil D. Bhagawan, IST, JNTUH, India Gamal Awad, National Research Centre, Egypt Gandhi Escajadillo Toledo, Pontifical Catholic University of Peru, Peru Hayssam Mohamed Ali, King Saud University, Egypt Jephias Mapuva, Bindura University, Zimbabwe Syakir Amir Ab. Rahman, International Islamic University Malaysia, Malaysia